A heparan-sulfate-bearing syndecan-1 glycoform is a distinct surface marker for intra-tumoral myeloid-derived suppressor cells - Thomas Welte (Elsevier, 2021)
Summary: Myeloid-derived suppressor cells (MDSCs) infiltrate cancer tissue, promote tumor growth, and are associated with resistance to cancer therapies. However, there is no practical approach available to distinguish MDSCs from mature counterparts inside tumors. Here, we show that a recently isolated thioaptamer probe (T1) binds to MDSC subsets in colorectal and pancreatic tumors with high specificity. Whole transcriptome and functional analysis revealed that T1-binding cells contain polymorphonuclear (PMN)-MDSCs characterized by several immunosuppression pathways, ROS production, and T cell suppression activity, whereas T1-non-binding PMNs were mature and nonsuppressive. We identified syndecan-1 as the T1-interacting protein on MDSCs and chronic myelogenous leukemia K562 cell line. Heparan sulfate chains were essential in T1-binding. Inside tumors PMN-MDSCs expressed heparan sulfate biogenesis enzymes at higher levels. Tumor-cell-derived soluble factor(s) enhanced MDSCs' affinity for T1. Overall, we uncovered heparan-sulfate-dependent MDSC modulation in the tumor microenvironment and identified T1 as tool preferentially targeting tumor-promoting myeloid cell subsets.